Machine learning and statistical prediction of pitching arm kinetics - Nicholson, K. F.; Collins, G. S.; Waterman, B. R.; Bullock, G. S. (The American Journal of Sports Medicine, 2021)
Background: Over the past decade, research has attempted to elucidate the cause of throwing-related injuries in the baseball athlete. However, when considering the entire kinetic chain, full body mechanics, and pitching cycle sequencing, there are hundreds of variables that could influence throwing arm health, and there is a lack of quality investigations evaluating the relationship and influence of multiple variables on arm stress.